Solving of the Workspace Boundary of Planar Parallel Mechanism based Modified PSO Algorithm - Ji Fangfang Zhao Xin (Jixie chuandong)
A new method for determining the workspace boundary of planar parallel mechanism by using improved particle swarm optimization (MPSO) algorithm is proposed. A general objective function is formulated to give the best value that the planar parallel mechanism reaches its limit point. The workspace boundary of the parallel manipulator can be constructed by finding these points by using MPSO, the MPSO method is used to obtain the mapping of workspace boundary of 3RRR planar parallel mechanism in order to verify the effectiveness of this method. At the same time, the influence of initial position on workspace search is studied. The results show that the selection of initial point is the key to solving workspace boundary. Compared with discretization method, MPSO search process is more efficient and the obtained workspace boundary points are accurate.